2013
DOI: 10.1123/jpah.10.3.437
|View full text |Cite
|
Sign up to set email alerts
|

Using Accelerometers in Youth Physical Activity Studies: A Review of Methods

Abstract: The increasing diversity of methods used to process and score accelerometer data for youth precludes comparison of results across studies. Decision rule reporting is inconsistent, and trends indicate declining standardization of methods. A methodological research agenda and consensus process are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
553
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 580 publications
(567 citation statements)
references
References 61 publications
6
553
0
8
Order By: Relevance
“…12:36-13:18: Lunch, independently eating bread with knife and fork). For practical reasons (complexity of data analysis and logistics), we chose to only measure for 2 days, instead of the recommended 7 days (Cain et al 2013). Patients were asked to wear the accelerometers at all waking hours, with the exception of bathing, showering and swimming.…”
Section: Study Protocol For Patientsmentioning
confidence: 99%
“…12:36-13:18: Lunch, independently eating bread with knife and fork). For practical reasons (complexity of data analysis and logistics), we chose to only measure for 2 days, instead of the recommended 7 days (Cain et al 2013). Patients were asked to wear the accelerometers at all waking hours, with the exception of bathing, showering and swimming.…”
Section: Study Protocol For Patientsmentioning
confidence: 99%
“…Given the high proportion of participants who reported engaging in these types of activities, accelerometry provided an incomplete measure of MVPA. Moreover, suggested MVPA accelerometer cut points for adolescents range considerably, and there is no consensus on which is most appropriate [36][37][38]. While the cut points used here were validated specifically for adolescent girls, the validation study found that cycling and step aerobics had poor calibration with accelerometers, and found a wide range of MET's in individuals for each level of accelerometer counts.…”
Section: Principal Resultsmentioning
confidence: 99%
“…The 10-minute blocks of energy expenditure were classified, based on their metabolic equivalent values, into physical activity intensities as follows; sedentary behaviour ≤ 1.5 times predicted basal metabolic rate, light intensity physical activity > 1.5 to <3.0 times predicted basal metabolic rate and moderate-to-vigorous intensity physical activity ≥ 3.0 times predicted basal metabolic rate. As there is still inconsistency between the use of 3 or 4 times resting energy expenditure as moderate-to-vigorous intensity physical activity threshold in children (Cain et al 2013), and most cut points in this study have been developed using a threshold of 3 times resting energy expenditure, this was used. Activity energy expenditure was determined by deducting basal metabolic rate, calculated using the Schofield equation, from measured energy expenditure.…”
Section: Data Reductionmentioning
confidence: 99%